2022
DOI: 10.3389/fpubh.2022.931425
|View full text |Cite
|
Sign up to set email alerts
|

The effect of living alone on the mental health of the economically active floating population during the COVID-19 pandemic

Abstract: BackgroundThe Coronavirus disease 2019 (COVID-19) pandemic broke out at the end of 2019 in China. Through a strict Zero-Tolerant strategy, the pandemic was nearly controlled in the first half of 2020, and production resumed in most regions of China. A survey was performed to explore the effect of living alone on the mental health of the economically active floating population (EAFP) in developed regions of China during the COVID-19 pandemic.MethodsThe online cross-sectional survey was conducted in work resumed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
3
1
Order By: Relevance
“…Financial stability can favor family formation, a significant milestone for many individuals [44]: for example, earnings were found to have an important influence on marriage timing [45]. Furthermore, the social distancing needed for the COVID-19 pandemic showed that living alone can strongly affect mental health [46]. For these reasons we expected cohabitation to be a protective factor for depressive symptoms, but we did not observe a significant association in this regard.…”
Section: Discussioncontrasting
confidence: 58%
“…Financial stability can favor family formation, a significant milestone for many individuals [44]: for example, earnings were found to have an important influence on marriage timing [45]. Furthermore, the social distancing needed for the COVID-19 pandemic showed that living alone can strongly affect mental health [46]. For these reasons we expected cohabitation to be a protective factor for depressive symptoms, but we did not observe a significant association in this regard.…”
Section: Discussioncontrasting
confidence: 58%
“…Among the respondents, there were 201 males and 320 females, spanning ages 18 to 85 years. To better characterize the cohort, we categorized them as young adults (ages [18][19][20][21][22][23][24], adults (ages [25][26][27][28][29][30][31][32][33][34][35], middle-aged individuals (ages 36-64), and older adults (ages >65). Females constituted 61.42% of the participants, while males accounted for 38.58%.…”
Section: Resultsmentioning
confidence: 99%
“…In a study conducted in the United States, it was found that residing in larger families had a resilience effect during the pandemic, while living alone had a negative impact on mental well-being [26]. Additionally, in China, when factors such as age, gender, and social status were analyzed alongside living alone, female loneliness and self-employment were identified as variables that negatively influence psychosocial well-being [27].…”
Section: Living Arrangement and Its Impact On Pandemic Time Mental He...mentioning
confidence: 99%
“…Social support has been identified as a protective factor against negative pandemic-related outcomes ( Xu and Zhang, 2022 ), with cohabitation associated with higher levels of life satisfaction ( Geprägs et al, 2022 ). A national survey revealed that 36% of respondents reported significant loneliness during the pandemic ( Weissbourd et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%